Egg Yolk-Free Vegan Mayonnaise Preparation from Pickering Emulsion Stabilized by Gum Nanoparticles with or without Loading Olive Pomace Extracts - Akcicek, Alican; Karasu, Salih; Bozkurt, Fatih; Kayacan, Selma (AMER CHEMICAL SOC, 2022)
The yolk-free mayonnaise was formed by Pickering emulsions stabilized by free and encapsulated olive pomace extracts (OPEs) in rocket seed [rocket seed gum nanoparticle (RSGNP)] and chia seed gum nanoparticles at different nanoparticle concentrations. The yolk-free mayonnaise and the control mayonnaise samples were compared in terms of appearance, microstructural, droplet size, emulsion stability, theological, oxidative stability, and sensory properties. The droplet size decreased by increasing the nanoparticle concentration in yolk-free mayonnaise samples. The yolk-free mayonnaise samples prepared with OPE-loaded gum nanoparticle showed shear-thinning, solid-like and recoverable characteristics, which increased as the increase in the nanopartide concentration. The emulsion stability and capacity increased by increasing the nanoparticle concentration in the yolk-free mayonnaise samples. OPE-loaded gum nanoparticle-stabilized yolk-free mayonnaise samples exhibited higher IP (induction period) values than the control samples. OPE-RSGNP 196 mayonnaise was observed to be the closest sample to the control sample with its sensory properties, general acceptability, and similar microstructural and theological properties. The results of this study indicated that Pickering emulsions stabilized by gum nanoparticles could be used as healthy alternatives to the egg yolk in conventional mayonnaise.
Keywords: SIZE DISTRIBUTION; FOOD APPLICATIONS; STARCH; OIL; FAT; FORMULATION; RHEOLOGY; DESIGN; TRENDS; Chemistry